Evaluation of nutritional state and sarcopenia in patients with vasculitis - Turhan, Okan; Halil, Meltem Gülhan (Acta Medica, 2025)
Vasculitides are systemic rheumatic diseases characterized by chronic inflammation, predisposing patients to a polymorbid state and profound metabolic disturbances. Among the most clinically relevant complications are malnutrition and sarcopenia, which frequently coexist and contribute to frailty, disability, and mortality. Malnutrition arises from reduced dietary intake, treatment-related gastrointestinal side effects, and inflammation-driven metabolic imbalance, while sarcopenia is defined as the progressive loss of muscle mass, strength, and function, and develops as a secondary complication of chronic inflammation, glucocorticoid exposure, renal impairment, and physical inactivity. Their prevalence is high in patients with vasculitis, and they are strongly associated with adverse outcomes. Early recognition is essential and requires structured screening of nutritional risk with validated tools, complemented by systematic evaluation of muscle strength and body composition. Evidence emphasizes that intervention should begin once risk or probable sarcopenia is identified, rather than awaiting definitive confirmation. Management is multidisciplinary, integrating medical nutrition therapy with adequate protein and energy intake, oral or enteral supplementation when necessary, and individualized exercise programs, particularly resistance training, to stimulate muscle synthesis and restore function. This review highlights the underlying mechanisms, diagnostic approaches, and evidence-based strategies for addressing malnutrition and sarcopenia in vasculitis, underscoring the importance of proactive and coordinated care to improve functional outcomes, quality of life, and prognosis.